Parental relationship satisfaction, reflective functioning, and toddler behavioral problems: A longitudinal study from pregnancy to 2 years postpartum - Salo, Saara Johanna; Lipsanen, Jari Olavi; Sourander, Johanna; Pajulo, Marjukka; Kalland, Mirjam (Frontiers in Psychology, 2022)
Parent relationship satisfaction and parental reflective functioning (PRF) are significant factors in the transition to first-time parenting and are likely to affect a child’s later well-being. However, little is known about their joint longitudinal effects from pregnancy onward. Starting in the prenatal period, this follow-up study of 1016 Finnish first-time parents (358 fathers and 658 mothers at baseline) examined the stability and the reciprocal associations between relationship satisfaction and PRF in predicting child behavioral problems (CBCL) at age 2. First, the results of the random-intercept cross-lagged panel models showed that both relationship satisfaction and PRF were stable from pregnancy onward for both mothers and fathers, with the exception of mothers’ prenatal PRF. Second, there were significant reciprocal associations between low prenatal PRF and low relationship satisfaction at age 1, and vice versa. Third, for both mothers and fathers, a low level of relationship satisfaction, but not PRF, predicted consistently higher levels of child behavioral problems at age 2. These results suggest that parent relationship satisfaction and PRF are stable but largely independent parental factors during the transition to parenthood. In addition, our results highlight the significant role of parent relationship satisfaction in predicting toddler behavior problems, which indicates the relevance of early relationship-orientated help for first-time parents.